Analisis Kinerja Karyawan Dengan Pelatihan Dan Disiplin Kerja (Studi Empiris Pada Kantor Pelayanan Bea Dan Cukai Tipe Madya Belawan Sumatera Utara) - Susi Handayani; Novia Rohmaiya Berutu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
Employee performance is performance not only seen as a result, but also with regard to independence, consistency with organizational values, understanding of issues related to responsibility, discipline and communicating well. The research approach used in this study is to use an associative and quantitative approach. The variables used in this study consist of training, work discipline, employee performance. The population in this study were all employees at the Belawan Intermediate Customs and Excise Service Office, amounting to 204 people, while the study sample was 67 employees. Data collection techniques in this study were questionnaires, interviews and documentation. Data analysis techniques using multiple linear regression, uiji t, f test and coefficient of determination (R-Square). The results showed that there was a positive and significant influence between training variables on employee performance, there was a positive and significant influence between work discipline variables on employee performance, there was a positive and significant influence between training variables and work discipline on employee performance at the Customs and Excise Service Office Middle Type Belawan.